Consumption pattern and consumers' opinion toward street food in Nakhon Si Thammarat province, Thailand - Khongtong, Jatuporn; Abdul Karim, Muhammad Shahrim; Othman, Mohhidin; Bolong, Jusang (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2014)
Street food in NST province is crucial for the people due to the changing of lifestyles. The consumers demand enhances the number of street vendors in the province. Nevertheless, there are vendors that are not practicing good hygienic compared to other province. The objectives of this study are to identify the pattern of street food consumption, and consumers' opinion towards the street food. Observation and in-depth interview were used to collect data. Ten respondents with various demographic backgrounds were interviewed on their experiences, and opinions toward street food. The data found that the street food consuming pattern was formed in six major themes: consumer characteristic, type of food, location, time of consuming, ways to consume and reasons of consuming. Additionally, the study also declared consumer's opinion on the problems related to street food. The finding aims local authority to have more understanding on the culture of street food consumption, and the problems that have been existed to find the appropriate improvement, and do not induce any conflict between local authority with street vendors and authority with consumers.